The Effect of Emotional Intelligence Skills by Flipped Classroom Method on the Patients’ Privacy in Nursing Students - Zahra, Maddah; Hossein, Bayat Amir; Yaghoub, Parandvar; Fatemeh, Martoob; Majid, khaze Seyed; Amin, Haghgoo (International Journal of Psychosocial Rehabilitation, 2020)
Privacy is one of the fundamental human rights that needs to be respected and observed especially in health care organizations. However, few studies have been conducted on training of observance of patient privacy.The purpose of this study was to determine The Effect of Emotional Intelligence Skills by Flipped Classroom Method on the Patients’ Privacy in Nursing Students .This quasi-experimental study was done in two experimental and control groups in 2018 in nursing students in Saveh, Iran. The intervention in the experimental group was performed in 9 sessions each lasting 90 minutes for 5 weeks. The control group did not receive any intervention. Data were collected using a 24-item questionnaire (i.e., Preservation and Observation of Patients’ Territory) before and after the intervention. Then, the data were analyzed by descriptive and inferential statistics using the SPSS software.Paired t-test showed that there was a statistically significant difference between patients’ privacy before and after the intervention (P = 0.0001), but, this test did not show a significant difference in the control group before and after the intervention (p = 0.352). Independent t-test showed that the mean scores of patients’ privacy increased after intervention in the experimental group compared to the control group and there was a statistically significant difference between the two groups (p = 0.0001).Based on the results of this study, it can be said that using new educational methods such as inverted classrooms, we can improve patient privacy in medical students.